Pelatihan Pembuatan Perjanjian untuk Menghindari Sengketa Hukum - Sri Hartini; Budiyono Budiyono; Budiman Setya Haryanto; Nur Wakhid (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIN Prof. K.H. Saifuddin Zuhri, 2021)
The lack Legal issues in the agreement process include leases, contracts, and accounts payable.Legal problems emerge due to carelessness and a lack of understanding of contract law. Lackof legal understanding has resulted in many fraud and embezzlement cases due to agreementsdisregarding a strong legal basis. Based on this phenomenon, the Community Service Team heldsocialization and education to reduce these problems. Implementing community service is carried out by the Blended method or a combination of implementation outside the network andwithin the network/offline and online. Online activities are carried out through zoom meetingsto provide material. Meanwhile, the practice of constructing legal agreements is carried out offline through face-to-face meetings with participants. Participants of community service are residents of Grendeng Village, Purwokerto. The service results show that before they get education about legal agreements, 90% of partners in contracting, leasing, buying, and selling do not use legal agreements and are only based on trust. The transfer of science and technology to partners regarding the complexities of the agreement includes rights, obligations, understanding, the meaning of the agreement, the purpose of the agreement, type of agreement, legal consequences, sanctions if violated, legal protection, settlement of agreement violations, and the practice of recognizing and making simple agreements directly. After holding community service, the partner understands the importance of agreements and can create simple agreements.